Cahaya Intensitas Rendah (10 lux) Berpengaruh pada Frekuensi Nafas dan Saturasi Oksigen Bayi Berat Badan Lahir Rendah: penelitian kuasi eksperimen satu grup - Sari, Ignasia Yunita; Prawesti, Indah; Kusumawati, Ardiyan Ida (Health Information : Jurnal Penelitian, 2022)
Babies with Low Birth Weight (LBW) are at risk of various health problems in the early stages of birth. Environmental conditions outside the womb cause stressors and affect their physiological functions, and environments with strong lighting can reduce the baby's adaptation process. The aim of the study was to determine the effect of low-intensity light intervention on the breathing frequency and oxygen saturation of LBW infants in the NICU room of Bethesda Hospital, Yogyakarta. The research design used a quasi experiment in one group with pre and post test designs. The total sample was determined using the quota method in March-September 2020, and a total of 20 respondents. Data collection by measuring respiratory frequency and oxygen saturation, before and after giving 10 lux low intensity light. After intervention with low intensity light, respiratory rate was 42.9x/minute, and oxygen saturation was 95.7%. Statistical test results on both variables with a p value <0.05. Low light intensity of 10 lux is statistically associated with decreased respiratory rate and increased oxygen saturation in infants with low birth weight.